2019
DOI: 10.1088/1361-6560/ab293b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 220 kHz insonation scheme on rt-PA thrombolytic efficacyin vitro

Abstract: Ultrasound-enhanced recombinant tissue plasminogen activator (rt-PA) thrombolysis is under development as an adjuvant to ischemic stroke therapy. The goal of this study was to design a pulsed ultrasound (US) exposure scheme that reduced intracranial constructive interference and tissue heating, and maintained thrombolytic efficacy relative to continuous wave (CW) insonation. Three 220 kHz US schemes were evaluated, two pulsed insonation schemes (15 cycles, 68 µs pulse duration, 33% or 62.5% duty cycle) and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Goyal et al (2017) also measured a higher degree of thrombolysis with 1 MHz pulsed ultrasound at 1.0 MPa peak rarefactional pressure with inertial cavitation than at 0.23 MPa peak rarefactional pressure with stable cavitation in an in vitro model of microvascular obstruction using perfluorobutane-filled, lipid-shelled microbubbles (Weller et al 2002) as a nucleation agent. However, Kleven et al (2019) observed more than 60% fractional clot width loss for highly retracted human whole blood clots exposed to rt-PA, Definity and 220 kHz pulsed or continuous wave (CW) ultrasound at an acoustic output with sustained stable cavitation throughout the insonification periods (0.22 MPa peak rarefactional pressure) (Fig. 6).…”
Section: Mechanisms Agents and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Goyal et al (2017) also measured a higher degree of thrombolysis with 1 MHz pulsed ultrasound at 1.0 MPa peak rarefactional pressure with inertial cavitation than at 0.23 MPa peak rarefactional pressure with stable cavitation in an in vitro model of microvascular obstruction using perfluorobutane-filled, lipid-shelled microbubbles (Weller et al 2002) as a nucleation agent. However, Kleven et al (2019) observed more than 60% fractional clot width loss for highly retracted human whole blood clots exposed to rt-PA, Definity and 220 kHz pulsed or continuous wave (CW) ultrasound at an acoustic output with sustained stable cavitation throughout the insonification periods (0.22 MPa peak rarefactional pressure) (Fig. 6).…”
Section: Mechanisms Agents and Approachesmentioning
confidence: 99%
“…Temperature rise was prominent in the ipsilateral bone along the transducer axis. The computational model is described in Kleven et al (2019).…”
Section: Cavitation Monitoringmentioning
confidence: 99%
“…The presence of standing waves produces acoustic field variations that are sensitive to changes in transducer position, excitation frequency or temperature (Huber et al 2011). The acoustic intensity of the ultrasound field is proportional to the square of the pressure amplitude when the ultrasound wavelength is much smaller than the transducer aperture (Kleven et al 2019). Under the plane wave approximation, the acoustic pressure is related to the intensity as follows: I = P 2 /2pc, where P is the peak acoustic pressure, p is the density and c is the speed of sound (Kinsler et al 2000).…”
Section: Experimental Approachesmentioning
confidence: 99%
“…In this paper, we have analyzed the nonlinear dynamics of the free bubble in the absence of coating (shell). Coated bubbles and most importantly lipid shell bubbles [76] are used in medical applications of ultrasound from SH imaging [40] to blood brain barrier opening [46] and thrombolysis [77]. The nonlinear behavior of lipid coating (e.g.…”
Section: Chaosmentioning
confidence: 99%